Additions to hyphomycete genus Pseudocercospora - and H.S.G. RAO, P.N. SINGH, R.N. KHARWAR (Indian Phytopathology, 2002)
P. anisomelicola var. ramosa var.nov., P. biophytiicola sp.nov. and P. clematicola sp.nov., collected on Anisomeles indica, Biophytum sensitivum and Clematis sp., respectively, in Uttar Pradesh, India, are described, illustrated and compared with related species.